Correction: Connexin 43 plays an important role in the transformation of cholangiocytes with Clonochis sinensis excretory-secretory protein and N-nitrosodimethylamine. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2019)
[This corrects the article DOI: 10.1371/journal.pntd.0006843.].